Risk factors associated with low birth weight - Diabelková, Jana; Rimárová, Kvetoslava; Urdzík, Peter; Dorko, Erik; Houžvičková, Andrea; Andraščíková, Štefánia; Drabiščák, Erik; Škrečková, Gabriela (Central European journal of public health, 2022)
OBJECTIVES: Low birth weight (LBW) is one of the major factors affecting child morbidity and mortality worldwide. Every day, approximately 800 women die from causes related to pregnancy and childbirth worldwide. Maternal ill health increases the risk of LBW. This study seeks to investigate determinants and incidence of LBW. METHODS: This study was conducted based on the medical records of mothers and their 1,946 infants born in 2016-2019 at the Department of Gynaecology and Obstetrics of Louis Pasteur University Hospital in Košice. Data on mothers and newborn infants were obtained from the Reports on mothers at childbirth. The inclusion criteria were singleton births and birth weight > 500 g. The exclusion criteria were twins or multiple births, congenital anomalies and stillbirths, birth weight ≥ 4,000 g or ≤ 500 g, and Roma ethnicity. Roma children are more likely to be born prematurely, with low birth weight. Roma mothers have different lifestyle. Univariate analysis was employed to evaluate the association between the independent variables and LBW. Variables that were found to be statistically significant were then further analysed using multivariable logistic analysis for each dependent variable. The implementation of the research was approved by the Ethics Committee. RESULTS: Of 1,946 newborns, 271 (13.90%) have low birth weight. The mean of birth weight at delivery was 3,068.62 (SD 671.16) grams. Factors that were associated with LBW were primary maternal education (OR = 2.98, 95% CI: 1.08-8.21, p = 0.034), marital status single (OR = 2.88, 95% CI: 1.68-4.94, p < 0.001), number of prenatal care visits less than 8 (OR = 1.62, 95% CI: 1.01-2.61, p = 0.047), and preterm birth (OR = 74.94, 95% CI: 45.44-123.61, p < 0.001). CONCLUSION: The reducing of LBW requires strategies to improve maternal lifestyle, maternal care before, during and after birth and to strengthen social support.
Keywords: prenatální péče; newborn; Risk Factors; low birth weight; risk factors; porodní hmotnost; Infant; Child; předčasný porod; Pregnancy; Prenatal Care; těhotenství; dítě; Premature Birth; novorozenec; lidé; ženské pohlaví; Birth Weight; Humans; Infant, Newborn; kojenec; rizikové faktory; Infant, Low Birth Weight; Female; novorozenec s nízkou porodní hmotností